Filmography of Philippine films, 1959-1989 - Junio, Arnulfo O.; Mendoza, Annella M.; Vallejo, Rosa M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1995)
This retrospective filmography deals with the popular Philippine feature films produced and/or exhibited in local movie houses from 1959 to 1989. Factual information on Filipino films was based entirely on secondary printed sources in the absence of the film itself. All pertinent articles in available issues of local and foreign newspapers, magazines, journals, annuals, and other materials published within the period 1959-1989 and possessed by various institutions, groups, and individuals were consulted.
Filmographic entries follow a simple alphabetical arrangement by film title. Under such scheme, titles are arranged in alphabetical order by the first word. After each title come the producer, director, year, actor 1, actor 2, actress 1, actress 2, genre, FIAF (classification number), prizes, and other production credits. There are 4,044 entries. A film with two, three (as in trilogy) or more episodes or stores and/or handled by different directors, however, has two or more entries depending on the number of episodes or stories.
This study does not purport to be conclusive nor authoritative. Nevertheless, utmost effort was exerted in gathering the filmographic information to make it a good source of materials for the study of Philippine film history, production, and documentation. In a way, this filmography continues the work of Carmencita Momblanco which listed films from 1909-1958.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Moving pictures--Philippines--Bibliography.